MARKETING INNOVATION IN NEWSPAPERS THROUGH DIGITALIZATION (GALA NEWSPAPER CASE STUDY - Putri, Gita Dhitawati; Purwanda, Eka (Manager : Jurnal Ilmu Manajemen, 2023)
The study in this research examines the digitalization of the marketing innovations in one of the newspapers published in Bandung, Gala Newspaper. Gala Newspaper is running under PT Motekar Atra Media. The research aims to comprehend and contribute the global picture of the Gala Newspaper marketing innovations in increasing the promotion and the sale digitally. In this research, the writer uses the theory stated by Cooper that a new product superiority is highly important in a competitive environment. The superiority cannot be separated from the development of the product innovations produced hence they actually have the superiority which then will make them win the competition. The method applied is the descriptive qualitative case study method to generate data from the competent source person. The data collection is done by doing the deep interview technique, the field observation and the literature study. The core of this study is for the Gala Newspaper marketing innovations to sustain through the digitalization of the marketing strategy innovations (product, price, promotion, distribution).